The construction of common treadmills significantly affects biomechanical and metabolic variables - Gidley, A. D.; Lankford, D. E.; Bailey, J. P. (Journal of Sports Sciences, 2020)
Surface compliance has been shown to affect leg stiffness and energetics. It is unknown if compliance differences between common treadmills would elicit such changes. Therefore, the purpose of this study was to determine if compliance design differences of common treadmills would affect the mechanics and energetics of running. Eleven runners ran at moderate, self-selected, matched belt speeds for three minutes on two treadmills: compliant (CT) and rigid (RT) decks. During the last minute of each trial, oxygen consumption and six markers describing the torso, thigh, shank and foot, and one marker to determine treadmill deflection were recorded. Leg stiffness, continuous relative phase (CRP) and CRP variability were calculated. Compared to RT, running on CT resulted in a significantly more compliant leg (8.591 kN/m > 9.063 kN/m), lower oxygen consumption (34.69 ml/kg•min < 36.86 ml/kg•min), different coordination patterns and greater variability, particularly during the push-off phase. These results are inconsistent with the literature because the deck of CT rebounds back at the runner during the absorption phase and away from the runner during the push-off phase. Therefore, care should be taken when using treadmills for research and comparing mechanical and energetic measures between studies.